Selective Forwarding Attacks against Data and ACK Flows in Network Coding and Countermeasures. (14th November 2012) - Zhang, Yuanyuan; Minier, Marine
Abstract : Network coding has attracted the attention of many researchers in security and cryptography. In this paper, a well-known attack selective forwarding attack will be studied in network coding systems. While most of the works have been dedicated to the countermeasures against pollution attacks where an attacker modifies intermediate packets, only few works concern selective forwarding attacks on data or acknowledgment (ACK) packets; those last ones are required in network coding. However, selective forwarding attacks stay a real threat in resource constraint networks such as wireless sensor networks, especially when selective forwarding attacks target the acknowledgment (ACK) messages, referred to as flooding attack . In the latter model, an adversary can easily create congestion in the network and exhaust all the resources available. The degradation of the QoS (delay, energy) goes beyond the capabilities of cryptographic solutions. In this paper, we first simulate and analyze the effects of selective forwarding attacks on both data flows and ACK flows. We then investigate the security capabilities of multipath acknowledgment in more details than in our original proposal (Zhang et al., 2011).